2012
DOI: 10.1161/circresaha.111.253229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CaMKII Phosphorylation of RyR2 Prevents Induction of Atrial Fibrillation in FKBP12.6 Knockout Mice

Abstract: Rationale Abnormal calcium release from sarcoplasmic reticulum (SR) is considered an important trigger of atrial fibrillation (AF). Whereas increased CaMKII activity has been proposed to contribute to SR leak and AF-induction, downstream targets of CaMKII remain controversial. Objective To test the hypothesis that inhibition of CaMKII-phosphorylated type-2 ryanodine receptors (RyR2) prevents AF initiation in FKBP12.6-deficient (−/−) mice. Methods and Results Mice lacking RyR2-stabilizing subunit FKBP12.6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 11 publications
(19 reference statements)
7
112
0
Order By: Relevance
“…Cardiac Electrophysiology. In vivo electrophysiology in mice was conducted as previously described (47). Briefly, intracardiac electrograms were recorded using a 1.1F octapolar catheter (EPR-800; Millar Instruments) inserted via the right jugular vein.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac Electrophysiology. In vivo electrophysiology in mice was conducted as previously described (47). Briefly, intracardiac electrograms were recorded using a 1.1F octapolar catheter (EPR-800; Millar Instruments) inserted via the right jugular vein.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that phosphorylations of RyR2 on serine-2814 and PLN on threonine-17 are increased after rapid atrial pacing in atrial myocytes and genetic inhibition of RyR2 phosphorylation on serine-2814 attenuates the incidence of atrial fibrillation (AF) induced by rapid atrial pacing (51). Accordingly, we examined the effects of Epac1 deletion on the initiation and maintenance of AF in the mouse model (Figure 8 and ref.…”
Section: Figurementioning
confidence: 99%
“…The conventional approaches of functional characterization of genes have been overexpression and knockout or knockdown studies, which provide valuable insights into gene function. 23,[61][62][63][64] The approaches are extremely powerful in the analysis of a specific gene function. 61 Efforts are underway to develop mouse knockout models of all known genes (https://www.komp.org).…”
Section: The Editors Recent Developments In Cardiovascular Genetics E89mentioning
confidence: 99%